2012
DOI: 10.1071/sr11225
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralisation from amended and unamended intensively managed tropical andisols and inceptisols

Abstract: Intensive vegetable production systems throughout South East Asia are characterised by large nutrient inputs and low nitrogen (N) use efficiencies. In Indonesia, intensive vegetable production is concentrated on volcanic highland soils starting from an altitude of around 700 m above sea level. We measured potential N mineralisation from soil organic matter and from several representative organic materials in Andisols and Inceptisols with andic properties from Central Java, Indonesia. Unamended soils and soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…These results were in line with the previous findings [45][46][47]. Hence, this strong correlation between the total N and NO3 − -N contents and the N mineralization rate represent the complex mineralization process that is influenced by different parameters and not only the residual added nitrogen [47]. From the calculated correlation between N mineralization rates and total N, it coincides with the finding of Widowati et al [47] who reported that N content of OAs may still be the best factor predicted difference in N mineralization behaviour.…”
Section: Nitrogen Mineralizationsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in line with the previous findings [45][46][47]. Hence, this strong correlation between the total N and NO3 − -N contents and the N mineralization rate represent the complex mineralization process that is influenced by different parameters and not only the residual added nitrogen [47]. From the calculated correlation between N mineralization rates and total N, it coincides with the finding of Widowati et al [47] who reported that N content of OAs may still be the best factor predicted difference in N mineralization behaviour.…”
Section: Nitrogen Mineralizationsupporting
confidence: 93%
“…Correlation studies showed a significant correlation between N mineralization rate and total N (%) and NO3 − -N contents of the OAs. These results were in line with the previous findings [45][46][47]. Hence, this strong correlation between the total N and NO3 − -N contents and the N mineralization rate represent the complex mineralization process that is influenced by different parameters and not only the residual added nitrogen [47].…”
Section: Nitrogen Mineralizationsupporting
confidence: 92%
“…The average excess water (EW) was 2073 mm yr -1 for the Wonosobo sites and 1275 mm yr -1 for the Kopeng sites, respectively. The IP and FP nitrogen balance results were highly positive, as the nitrogen fertilizer was heavily applied (Widowati et al 2012) (Table 4). The average PNC values of IP and FP were significantly different (P < 0.05).…”
Section: Estimation Of No 3 Concentration In the Soil Water At 1 M Depthmentioning
confidence: 95%
“…Excessive N fertilizer application is therefore very common, while N use efficiency is often low. Data gathered from farmers' practices (Widowati et al 2012), revealed an average ANUE value 16% for two consecutive years; therefore, more than 80% of N added is susceptible to loss. Application of N fertilizer in excess of crop requirements can result in the accumulation of NO 3 -N in the soil profile (Gillard et al 1995;Malhi et al 2001).…”
Section: Soil Sampling For Physical Properties and Mineral N Profilesmentioning
confidence: 99%
See 1 more Smart Citation